Phylogenetic Patterns of Extinction Risk in the Endemic Flora of a Mediterranean Hotspot as a Guiding Tool for Preemptive Conservation Actions - Molina-Venegas, Rafael; Ramos-Gutiérrez, Ignacio; Moreno-Saiz, Juan Carlos (Frontiers in Ecology and Evolution, 2020)
Climate change is a major driver of biodiversity decline with pervasive effects in biodiversity hotspots, where many endemic and threatened species thrive. However, the biological drivers of extinction susceptibility remain largely elusive, which hampers the implementation of effective conservation policies. Here, we advocate for the use of phylogenies as a complementary tool to inform policy makers. If we assume that the traits that determine extinction susceptibility are somewhat evolutionarily conserved, identifying the clades that accumulate a disproportionate amount of threatened species may help to mitigate potential increases in extinction risk among currently unthreatened species in these clades, even if the underlying biological drivers are unknown. We focused on the complete endemic angiosperm flora of a Mediterranean hotpot (Iberian Peninsula) to examine phylogenetic patterns in extinction risk expressed as IUCN categories (Least Concern “LC”, Near Threatened “NT”, Vulnerable “VU”, Endangered “EN” and Critically Endangered “CR”) using alpha and beta diversity metrics, comparative methods and a “hot node” approach. Phylogenetic diversity was significantly low for EN species and marginally significant for NT and CR, while LC and VU categories showed random pattern. Phylogenetic beta diversity (PBD) between IUCN categories was intermediate (0.40 – 0.61) and predominantly due to the “true” turnover component of PBD. Phylogenetic turnover was significantly low between NT–VU and VU–EN, suggesting that closely-related species tend to show different threat status. In contrast, the comparisons involving the CR category sit towards the higher tail of the distribution, indicating a somewhat higher degree of clade specificity for CR species. In line with these patterns, phylogenetic signal in extinction risk was rather low (lambda = 0.23). Several of the “hot” clades that accumulated a significantly high number of species with the same threat status were specific to certain IUCN categories, yet few of them were observed across the categories. Most notably, the Caryophyllales stood out as the main threat-accumulating lineage, particularly within the Plumbaginaceae. All in all, our results indicate that few phylogenetic clades concentrate a great fraction of the extinction-risk gradient in the endemic flora of the western Mediterranean, and monitoring programs should pay particular attention to these extinction-prone lineages.